2022
DOI: 10.3389/fpsyg.2022.876116
|View full text |Cite
|
Sign up to set email alerts
|

Do Attitudes, Mental Health Status, and Interpersonal Factors Predict COVID-19 Vaccine Hesitancy at the Early Phase of the Pandemic? A Longitudinal Study in Chinese College Students

Abstract: PurposeThe present study examined whether and how attitudes toward the COVID-19 vaccine (i.e., safety, efficacy, and price), mental health statuses (i.e., perceived stress and depression), and interpersonal factors (i.e., online social support, perceived social support) would predict COVID-19 vaccine hesitancy.Patients and methodsThe two-wave longitudinal surveys were conducted in December 2019 and 2020 in Chinese medical college students (N = 194). Well- validated measures were used, including the Perceived S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…We found that social support contributes to increased vaccination intention. This mirrors findings from studies of younger adult populations where online social support increases COVID-19 vaccination intention [ 30 ], and loneliness decreases the likelihood of engaging in preventative behaviours for COVID-19 [ 31 ]. Our measure of social support was collected approximately 7 months prior to all other measures in our study which gives more ground for a causal relationship with vaccination intention.…”
Section: Discussionsupporting
confidence: 77%
“…We found that social support contributes to increased vaccination intention. This mirrors findings from studies of younger adult populations where online social support increases COVID-19 vaccination intention [ 30 ], and loneliness decreases the likelihood of engaging in preventative behaviours for COVID-19 [ 31 ]. Our measure of social support was collected approximately 7 months prior to all other measures in our study which gives more ground for a causal relationship with vaccination intention.…”
Section: Discussionsupporting
confidence: 77%
“… 42 , 43 It seems that stress can prompt negative cognitive responses, such as negative behavioural ones. 41 The non-significance of our results could be attributed to the period when the survey was performed. Indeed, prior studies have demonstrated that vaccine intent changes over time.…”
Section: Discussionmentioning
confidence: 73%
“…Students with high stress levels, and who reported more severe depressive symptoms, were more susceptible to have a negative perception of the SARS-CoV-2 vaccines. 41 Further studies indicated that individuals with poor mental health had decreased intentions to adopt health-related behaviours. 42 , 43 It seems that stress can prompt negative cognitive responses, such as negative behavioural ones.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants were university students, for whom living in shared student accommodation is the most important way of living, followed by living at home, and classmates and family members are the main sources of social support. A study has found that social support was a significant facilitator of vaccine acceptance (Wu, Wang, et al, 2022 ), so it is not difficult to understand that not living alone students with more support had better vaccine acceptance. Fourth, students with chronic disease had lower vaccination attitude scores than those without chronic disease.…”
Section: Discussionmentioning
confidence: 99%